Evaluation of antimicrobial regimens for treatment of experimental penicillin- and cephalosporin-resistant pneumococcal meningitis. - Friedland, I R (1993)
The most appropriate therapy for meningitis caused by Streptococcus pneumoniae strains resistant to the extended-spectrum cephalosporins is unknown. We evaluated ceftriaxone, vancomycin, and rifampin alone and in different combinations and meropenem, cefpirome, and clinafloxacin alone in the rabbit meningitis model. Meningitis was induced in rabbits by intracisternal inoculation of one of two pneumococcal strains isolated from infants with meningitis (ceftriaxone MICs, 4 and 1 microgram/ml, respectively). Two doses, 5 h apart, of each antibiotic were given intravenously (except that ceftriaxone was given as one dose). Cerebrospinal fluid bacterial concentrations were measured at 0, 5, 10, and 24 h after therapy was started. Clinafloxacin was the most active single agent against both strains. Against the more resistant strain, ceftriaxone or meropenem alone was ineffective. The combination of vancomycin and ceftriaxone was synergistic, suggesting that this combination might be effective for initial empiric therapy of pneumococcal meningitis until results of susceptibility studies are available.